Vaccinium uliginosum L. (bog bilberry) and the search for its alleged toxicity: a review - Vaneková, Zuzana; Holloway, Patricia; Rollinger, Judith M. (Frontiers in Toxicology, 2024)
Bog bilberry (Vaccinium uliginosum L.) is a wild-growing berry native to all circumboreal regions. There is however a significant discrepancy in the uses of bog bilberry fruits around the world. There exists a strong prejudice against the use of these berries in many European countries as well as a few incidences of poisoning reported between 1906 and 1944. In Asia and North America, this fear is completely absent from the local knowledge and the bog bilberry is valued as an excellent food and medicinal plant. There has been a lack of research on the topic in the last 50 years and thus the presumed toxicity remains unproven. This review aims to gather the conflicting information from all regions where bog bilberry grows and present them in a critical way to elucidate the possible explanations for the discrepancies. There are several possible explanations for the alleged toxicity of the bog bilberry, including a fungal infection of the fruits, individual intolerance or accidental poisoning by a different plant species; the local names meaning “drunk, inebriating, vomit-inducing berry” may be related to the alcoholic drinks made from them. This review highlights the gap in knowledge and serves as a theoretical framework for future research.